2012
DOI: 10.2478/v10045-012-0011-x
|View full text |Cite
|
Sign up to set email alerts
|

New Record of Powdery Mildew on Acacia Mangium Willd. in India

Abstract: Acacia mangium Willd. is one of the major tree species used in plantation forestry programs throughout Asia and the Pacific. The tree legume is prone to various seedling and foliage diseases found in nurseries and while in nurseries. This paper reports the incidence of powdery mildew caused by Oidium sp. on seedlings of A. mangium, maintained in root trainers and nursery seed beds of the Rain Forest Research Institute situated in Jorhat, Assam (India). This is the first report of powdery mildew on A. mangium f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…During the study period, the common factors affecting seedling health were Powdery mildew (Fungal disease caused by Podosphaera xanthii ) and Cottony cushion scale (Insect pest, Icerya purchase ), where A. etbaica and A. asak were the least affected species, respectively. Likewise, Borah et al, (2012) also found powdery mildew affecting Acacia species in nursery and Royal Botanic Gardens, Kew in its Bulletin Vol.1889 (32) stated cottony cushion scale loving Acacia. However in general, all of the species were affected from mild to medium levels but managed to grow and survive effectively.…”
Section: Resultsmentioning
confidence: 99%
“…During the study period, the common factors affecting seedling health were Powdery mildew (Fungal disease caused by Podosphaera xanthii ) and Cottony cushion scale (Insect pest, Icerya purchase ), where A. etbaica and A. asak were the least affected species, respectively. Likewise, Borah et al, (2012) also found powdery mildew affecting Acacia species in nursery and Royal Botanic Gardens, Kew in its Bulletin Vol.1889 (32) stated cottony cushion scale loving Acacia. However in general, all of the species were affected from mild to medium levels but managed to grow and survive effectively.…”
Section: Resultsmentioning
confidence: 99%